Development of microfluidic device and electronic infusion system to fabricate microfiber of alginate and carbon nanotube - Salman, Abdulsalam Ali Ahmed; Fhong Soon, Chin; Pao Lim, Gim (International Journal of Applied Power Engineering (IJAPE), 2023)
A novel microfluidic device and electronic infusion system for carbon nanotube-calcium chloride alginate microfibers are presented in this study. The microfluidic device was designed using Google SketchUp and 3D printing, and the electronic infusion system-controlled alginate solution flow to the calcium chloride jar—the silicon-PDMS microfluidic device produced calcium alginate microfibers with carbon nanotubes. The device to emulsify the two fluids was modeled in COMSOL Multiphysics. The microfluidic device and calcium chloride jar received juice from the syringe pump via a high-flow infusion pump (100, 150, and 200 rpms). Field emission scanning electron microscopes (FE-SEM), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, and X-ray diffraction analysis (XRD) detected highly concentrated microfibers with sizes from 10 to 100 um. I-V characterization showed that sodium alginate's carbon nanotubes at 5%, 6%, and 7% produced fiber sizes between 16.6 and 30 ums. Compared to pure alginate microfibers, those with carbon nanotubes and calcium chloride had higher mechanical strength and electrical conductivity. This study shows that the developed system can produce advanced microfibers with improved properties for various applications.